2022
DOI: 10.33019/electron.v3i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Rancang Bangun Alat Pendeteksi Status Pentanahan pada Instalasi Listrik Bangunan Berbasis Arduino Mega 2650 Pro

Abstract: Sistem pentanahan merupakan hal yang sangat penting pada suatu instalasi listrik bangunan. Stop-kontak merupakan komponen instalasi listrik yang berfungsi sebagai jalur suplai listrik ke peralatan elektronik dimana pada aturan PUIL 2000 harus terhubung ke sistem pentanahan bangunan. Seiring bertambahnya usia instalasi sebuah bangunan, maka akan terdapat sistem pentanahan yang mengalami degradasi. Pada penelitian ini telah dibuat alat pendeteksi pentanahan pada stop-kontak untuk mengetahui terhubungnya stop-kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The results show very low power consumption, low cost, highly reliable and compact design, achieving a high level of autonomy for over two years with only one 3.3 V/2600 mAh battery. Another study used ZMPT101b, AC712 and Arduino as microcontrollers to develop a grounding status detection tool (Corio et al 2022). The results showed that the tool's duration reaches 10 h non-stop per day, which is a long enough time to use for checking the grounding condition of a building.…”
Section: Resultsmentioning
confidence: 99%
“…The results show very low power consumption, low cost, highly reliable and compact design, achieving a high level of autonomy for over two years with only one 3.3 V/2600 mAh battery. Another study used ZMPT101b, AC712 and Arduino as microcontrollers to develop a grounding status detection tool (Corio et al 2022). The results showed that the tool's duration reaches 10 h non-stop per day, which is a long enough time to use for checking the grounding condition of a building.…”
Section: Resultsmentioning
confidence: 99%